A new triadic creative role for advertising industry: a study of creatives' role identity in the rise of social media advertising. Issue 2 (4th May 2018) - Lee, P. Y.; Lau, K. W.
ABSTRACT: Within the social networks online, consumers are no longer adopting a passive role in relation to dominant media; they have become a part of the media, constructing and promoting cultural meanings and values for consumption within their consumer culture. In this new era, advertising creatives were having increasingly direct contact with clients rather than depending on account managers. However, the question of how advertising organizations need to change in response to this changing environment has not been discussed extensively. Building upon the key experiences of advertising creatives in this empirical research, a triadic structure of advertising creatives' emergent role that was identified from the analyses of in-depth interview data in different types and levels of current advertising organizations. The contributions to both theory and practice in advertising and organizational studies are examined. The triadic role of advertising creatives identified in this study help to shape contemporary advertising creatives' identities in the social media advertising era, providing insights into employee perspectives on organizational roles. Although this study only offered a micro-level perspective on advertising creatives' practices and advertising organizations, which is still relatively rare in advertising and organizational literature.